(untitled) (Research, Society and Development, 2021)
The described neurological symptoms associated with pesticide exposure include memory and concentration problems. Most experimental studies of the association between dichlorophenoxyacetic acid (2,4-D) and neurotoxicity have focused on brain development, and few have been conducted in adult animals. The aim of this study was to assess whether chronic oral or inhalation exposure to 2,4-D affects object recognition memory in adult rats. Forty albino Wistar rats were used and distributed into 4 groups (n = 10): I: animals nebulized with distilled water; O: animals receiving feed treated with nebulized distilled water; DI: animals nebulized with 9.28 x 10-3 grams of active ingredient per hectare (g.a.i./ha) of 2,4-D; and DO: animals receiving feed treated with 9.28 x 10-3 g.a.i./ha of nebulized 2,4-D. The animals were exposed for 6 months. To assess recognition memory, the object recognition test was used. Compared to control animals, animals exposed to 2,4-D spent less time exploring objects (p <0.05) and obtained an object recognition index score of -1. Route of exposure to 2,4-D had an effect only on the time spent exploring objects, which was shorter in animals exposed orally. Chronic exposure to a high concentration of 2,4-D alters the ability of adult animals to recognize objects.